1979
DOI: 10.3109/08860227909064912
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics During Hemodialysis, Sequential Ultrafiltration and Hemofiltration

Abstract: Circulatory parameters were determined by cardiac catheterization in patients on maintenance hemodialysis. They were studied in three groups during conventional hemodialysis, sequential ultrafiltration and hemofiltration. All three groups revealed significant reduction of cardiac output, stroke volume, pulmonary artery pressure and plasma volume. In the hemodialysis group hemodynamic parameters were unstable; specifically, hypotension, increased heart rate, and only minimal increase of peripheral resistance we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 9 publications
4
28
0
1
Order By: Relevance
“…These results are in accordance with invasive hemodynamic studies of hypotension during hemodialysis." The hemodynamic responses to ultrafiltration differ from those following dialysis; 31 …”
Section: 02) With Changes In Total Peripheral Resistance (Atpr Grapmentioning
confidence: 99%
“…These results are in accordance with invasive hemodynamic studies of hypotension during hemodialysis." The hemodynamic responses to ultrafiltration differ from those following dialysis; 31 …”
Section: 02) With Changes In Total Peripheral Resistance (Atpr Grapmentioning
confidence: 99%
“…Since blood was purified at first in both methods, the circulating blood com partment was affected most. It is well known that the circulating blood volume decreases during both methods [3,5]. The change in serum protein concentration was measured in a separate experiment to estimate the change in circulating blood volume [5], A solid decrease in circulating blood volume was found in both methods, but the change was greater in HD.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the following merits re ported on HF: the decrease of blood osmolal ity is less [5]; the decrease of circulating blood volume is less, and the asymptomatic re moval of excess body fluid is possible [3][4][5][6], Recently, Shaldon et al [6] reported the rela tionship between sodium flux in HD and HF. They concluded that, although the urea filtra tion rate and urea clearance were higher in HF than HD to compensate for shorter treat ment time, significantly less hypotension de veloped owing to sodium flux in HF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which hemofiltration achieves this improved vascular stability has been investigated by numerous authors [19][20][21][22][23] and all report an increase in peripheral resistance as the mechanism by which the blood pressure is maintained ( fig. 3).…”
mentioning
confidence: 99%